Synthesis and Antimicrobial Activity of 2,5-Disubstituted 1,3,4-Oxadiazole Derivatives - ILANGO, K.; VALENTINA, P.; GUPTA, VIVEK (Asian Journal of Chemistry, 2010)
A series of 2-(quinolin-8-yloxymethyl)-5-aryl-1,3,4-oxadiazole [3a-3j] were synthesized. All the compounds were characterized by analytical and spectral analysis. The antibacterial and antifungal activities were screened for all the compounds. The antimicrobial activity revealed that the compounds 3c, 3g and 3h showed significant antibacterial activity and 3d, 3f and 3i exhibited better antifungal activity.